Analisis Kinerja Keuangan KSP Kopdit Obor Mas ditinjau dari Analisis Pearls dalam Kerangka Resource Base View - Krowin, Maria Trappistin Ose; Sanga, Konstantinus Pati; Da Rato, Elisabeth Yessi (Jurnal Projemen UNIPA, 2026)
This study aims to analyze the financial performance of KSP Kopdit Obor Mas using the PEARLS method (Protection, Effective Financial Structure, Asset Quality, Rates of Return and Cost, Liquidity, Signs of Growth) and to examine its relevance within the Resource Based View (RBV) framework. The research employed a descriptive method with both qualitative and quantitative approaches. Data were collected through observation, interviews, documentation, and cooperative financial reports from the Annual Member Meeting (RAT) for the period 2022–2024. The results indicate that the Protection aspect is categorized as healthy, as the risk reserve ratio is sufficient to cover delinquent loans. The Rates of Return and Cost aspect also shows good performance due to stable operational cost efficiency. However, weaknesses were found in the Effective Financial Structure, Asset Quality, and Signs of Growth aspects, particularly in the declining membership growth. From the RBV perspective, the cooperative possesses valuable and rare resources in the form of strong risk management capability and operational efficiency, but it has not fully developed a strong capital structure and asset quality to achieve sustainable competitive advantage. Therefore, the cooperative should improve credit management, strengthen institutional capital, and enhance membership growth to maintain long-term financial sustainability.